Complete mitochondrial genome of the vulnerable malabar pufferfish Carinotetraodon travancoricus (Tetraodontiformes, Tetraodontidae). Issue 2 (3rd July 2018) - Liu, Bingjian; Zhu, Kehua; Liu, Yifan; Jiang, Lihua; Lü, Zhenming; Liu, Liqin; Zhang, Weinan; Liu, Zhu; Duan, Wen; Gong, Li
Abstract: Carinotetraodon travancoricus was classified as vulnerable on the IUCN Red List due to habitat loss and overharvesting for the aquarium trade. To gain its molecular information and thus contribute to help in conserving this vulnerable species, we determined the complete mitochondrial DNA of the C. travancoricus . The size of the molecule is 16, 542 nucleotides, containing 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, a putative control region, and 1 origin of replication on the light-strand. The overall base composition includes C(28.8%), A(28.5%), T(27.1%), and G(15.6%). Moreover, the 13 PCGs encode 3800 amino acids in total. The result of the phylogenetic tree supports C. octofasciatus has a closest relationship with Tetraodon nigroviridis .